Cognitive processing of anaphoric encapsulation and coreference in native Spanish speakers: an experimental approach with eye tracking - Loureda Lamas, Óscar; Teucher, Mathis; Cruz, Adriana; Hernández Pérez, Celia; Gelormini-Lezama, Carlos (Discourse processes, 2026)
This empirical study examines the cognitive processing of anaphoric encapsulation in comparison with coreferential anaphora, focusing on the impact of antecedent complexity and noun phrase informativeness. Data from an eye-tracking experiment involving 448 native Spanish speakers provide evidence regarding different types of lexical relations in discourse. The contribution presents three key findings: (1) processing encapsulating and coreferential expressions requires similar cognitive effort even though they retrieve antecedents of different complexity, (2) the degree of informativeness of the anaphoric noun phrase plays a pivotal role in relational processing, and (3) the processing asymmetry between both encapsulating and coreferential expressions (associated with longer processing times) and their linguistic context (associated with shorter processing times) is greater in recategorizing relations than in categorizing ones.